Asymptomatic lymphatic filariasis in an elderly patient from Bako, Sarawak: A case report and public health implications - Romano, Ngui; Pangkas, Johnny; Chai, Ping Tze; Siti Farah Norasyikeen, Sidi Omar; Timothy Adrian, Jinam; Lim, Siong Hee; Khatijah, Yaman; Tan, Tiong Kai; Lim, Kai Joo; Neilson Richard, Seling; Sam Froze, Jiee (Malaysian Society of Parasitology and Tropical Medicine., 2026)
Lymphatic filariasis (LF) remains a significant public health challenge in many tropical regions where the disease is endemic. In Malaysia, LF is found in small pockets across the country. Asymptomatic carriers play a critical role in transmission but are often undetected. This report details an investigation of an asymptomatic filariasis reported by local health authorities involving an 83-year-old female patient residing in the Bako area, Sarawak. Despite being immobile due to a stroke, routine screening identified an infection with Brugia malayi through microscopy and a rapid diagnostic test. Interestingly, the patient exhibited no acute or chronic symptoms typically associated with filariasis. Contact tracing among her family members revealed that her son was also infected. Both patients received treatment with diethylcarbamazine (DEC) at a dosage of 6 mg/kg, along with albendazole 400 mg and ivermectin 12 mg. Preventive measures included health education, entomological studies, and the implementation of a ‘Test & Treat Filariasis’ program in the village. By documenting both the index case and a secondary asymptomatic case within the same household, the study provides a strong example of how routine screening and contact tracing can identify hidden sources of infection. This adds significant value to LF elimination strategies and emphasizes the importance of community-level surveillance programs. Coordinated efforts by health authorities, including contact tracing, environmental assessments, and targeted treatment, are essential for controlling the spread of LF and safeguarding public health.